The Disparity between Long-Term and Short-Term Forecasted Earnings Growth - DA, Zhi (Institutional Knowledge at Singapore Management University, 2008)
We find the disparity between long-term and short-term analyst forecasted earnings growth is a robust predictor of future returns and revisions in long-term forecasted earnings growth. After adjusting for industry characteristics, stocks whose long-term earnings growth forecasts are far above or far below their implied short-term forecasts for earnings growth have negative and positive subsequent risk-adjusted returns, respectively. Despite the importance of conditioning on short-term forecasted earnings growth, these returns are not driven by earnings momentum. Instead, consistent with investors having limited attention, predictable revisions in long-term analyst forecasts appear to induce return predictability.